Prospective Process Validation Study of Glibenclamide 2.5 mg Tablets - Patil, Prashant B; Chatap, Vivekanand K; More, Mahesh P; Khan, Zamir G (Current Research in Pharmaceutical Sciences, 2018)
The present study provides a high degree of assurance that a specific process for manufacturing of Glibenclamide Tablets will consistently produce a product meeting its predetermined quality attributes and specifications. It mainly comprises the stages to be followed to evaluate and qualify the acceptability of manufacturing process of Glibenclamide 2.5 mg tablets. The process is limited to the three batches manufactured of specific batch size with specified equipments and control parameters for tablets. It involves All parameters related to the each step were evaluated by respective standard test involved in the manufacturing. Sampling, testing plan and acceptance criteria for each step were monitored. The analytical results of all stages were found to be within the acceptable limit. Other tests related to compression such as hardness, thickness, disintegration and dissolution for all three batches were found within the acceptable limit.